DNA primase polypeptide 1 (PRIM1) involves in estrogen‐induced breast cancer formation through activation of the G2/M cell cycle checkpoint - Lee, Wei‐Hwa; Chen, Li‐Ching; Lee, Chia‐Jung; Huang, Chi‐Cheng; Ho, Yuan‐Soon; Yang, Po‐Sheng; Ho, Chi‐Tang; Chang, Hang‐Lung; Lin, I‐Hsuan; Chang, Hui‐Wen; Liu, Yun‐Ru; Wu, Chih‐Hsiung; et al. (International journal of cancer, 2019)
The DNA primase polypeptide 1 (PRIM1) is responsible for synthesizing small RNA primers for Okazaki fragments generated during discontinuous DNA replication. PRIM1 mRNA expression levels in breast tumor samples were detected by real‐time PCR analysis. Xenografted tumor model was established to study the carcinogenic role of PRIM1 and its potential therapeutic applications. The average PRIM1 mRNA (copy number × 103/μg) expression was 4.7‐fold higher in tumors than in normal tissue (*p = 0.005, n = 254). PRIM1 was detected preferentially at a higher level (>40‐fold) in poorly differentiated tumor tissues (n = 46) compared with more highly differentiated tumors tissues (n = 10) (*p = 0.005). Poor overall survival rate was correlated to the estrogen receptor positive (ER+, n = 20) patients with higher PRIM1 expression when compare to the ER− (n = 10) patients (Chi Square test, p = 0.03). Stable expression of PRIM1‐siRNA in the ER+ BT‐474 cells‐xenograft tumors significantly reduced tumor volume in SCID mice (*p = 0.005). The anti‐tumoral effects of inotilone isolated from Phellinus linteus was tested and had significant effects on the inhibition of PRIM1 protein expression in ER+ breast cancer cells. In vivo study was performed by administering inotilone (10 mg/kg, twice a week for 6 weeks), which resulted in significantly reduced BT‐474‐xenografted tumor growth volume compared with control (n =5 per group, *p < 0.05). This study provides evidences for the prognostic effects of PRIM1 with poor overall survival rate in the ER+ patients and will be valuable to test for therapeutic purpose. What's new? Breast cancer formation is a gradual process that arises due to uncontrolled DNA replication in the initial stages. Here the authors find that PRIM1, the smallest subunit of the DNA primase complex responsible for synthesizing small RNA primers during DNA replication, was upregulated in breast cancer samples as compared to healthy tissue. PRIM1 levels negatively correlated with survival in women with estrogen‐positive breast cancer, indicating potential prognostic value of measuring PRIM1 levels in future clinical applications.